Methods of Strength Development in Boys of Primary School Age Using Active Games - С. І. Марченко; В. А. Іщенко (OVS LLC, 2016)
The research objective is to analyze the effect of games on the dynamics of strength development in boys of the second-fourth grades. Research methods: theoretical analysis and collation of scientific and methodological literature, method of control testing, pedagogical experiment, methods of mathematical statistics. Research results. The paper addresses the feasibility of further scientific substantiation for the effect of the number of games, the number of repetitions, the intervals of rest and their interrelation on the change in the strength indicators for boys of primary school age. The study has revealed that strength development requires that the pupils of the second and the third grades perform four games, while the pupils of the fourth grade - five games. The number of repetitions for the pupils of the second grade is one and two, for the pupils of the third grade - two, and for the boys of the fourth grade - three, with 40-second intervals for rest. The most effective development manifests in the second and the fourth grades during 20 classes, and in the third grade -during 30 classes. After that, it is advisable to use other means. The game duration varies from two to five minutes. Conclusions. The results obtained during the experiment give reason to recommend that primary school teachers, coaches and parents use active games in physical education, sports training and individual motor activity of boys of primary school age. These games should aim at developing strength abilities, both purposefully and in complex with regard to the duration and pace (intensity) of their performance.